PENYELESAIAN KEPEMILIKAN KEWARGANEGARAAN GANDA DALAM PEMILIHAN KEPALA DAERAH KABUPATEN SABU RAIJUA (Putusan MK Nomor 135/PHP.BUP-XIX/2021) - Amor Ghozi; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2021)
The execution of the Indonesian state framework with a popularity based framework needs the appointment of local heads chosen by individuals in the district or area. The Political Decision Commission as the coordinator of the territorial head political race controls the execution of concurrent local head races in all areas of the Republic of Indonesia which were addressed in 2020 prior. Yet, there are cases connecting with double citizenship status in the choice of the Sabu Raijua official couple, East Nusa Tenggara. Situate Nationalist Riwu Kore up-and-comer Official number 2, demonstrated to have Indonesian and American citizenship. Situate Nationalist Riwu Kore subsequent to being dictated by KPU has the privilege to be a contender for official with the most noteworthy vote. In the choice of the Sacred Court Number 135/PHP.BUP-XIX/2021, the Established Court pronounced the preclusion of applicant number 2 Arrange Loyalist Riwu Kore and Thobias Ully from the appointment of Official and Representative Official of Sabu Raijua Rule. Subsequent to pronouncing preclusion the Sacred Court asked to re-vote..